Posture, proximity, and positionality: the power of community engaged service-learning in public health leadership education - Chu, Jocelyn C.; Marrero, Abrania (Frontiers in Public Health, 2025)
IntroductionPublic health leadership is a call to action, drawing us nearer to the individuals and communities burdened by health disparities and social injustice. Reimagining public health leadership to center health equity entails collective and community engaged applied practice, premised on humility, shared power, and life-long learning. Public health education has a unique imperative to offer experiential, transformative opportunities for students to learn and practice more adaptive approaches to public health action.MethodsThe Community Engaged Learning Fellowships at Harvard T. H. Chan School of Public Health support students and postdoctoral trainees to partner with organizations and implement co-designed community engaged projects. Through a cohort learning model, fellows engage in field-based projects with learning objectives centered on assuming the posture of a learner, proximity to community partners, and critical reflection around positionality and broader structural determinants of health. Qualitative data evaluating fellows’ learnings were collected. Responses from nine cohorts of fellows over 6 years (2018–2024) were analyzed thematically to reveal key insights into fellows’ overall learning experiences.ResultsFellows expressed the need to enact humility, relationality, and the centering of community expertise as values that could shift power away from themselves and toward community-identified priorities and decision-making. Embodying attitudes of authenticity and flexibility was central to fellows’ perceptions of this more equitable community engaged practice, ensuring that project goals, timelines, and unanticipated challenges, for example, reflected their partners’ agendas and lived experiences. Importantly, these deferential forms of service still contributed meaningfully to fellows’ learnings. Often, instead of holding on to preconceived project expectations, fellows practiced the skill of listening to learn and trust building to identify co-creative forms of problem-solving.Discussion and implicationsOur findings reinforce the importance of community engaged service-learning as a pedagogical strategy in public health leadership development, one that instills values, attitudes, and skills that are premised on leaders becoming “learners.” Community engaged service-learning cultivates a practice that decenters self-interests, uplifts community expertise, values authentic relationships, and promotes more collective forms of decision-making. Ensuring these opportunities are available in graduate education can foster commitments to community partnerships premised on equity and service in future leaders.